Praise of the Prophet Muḥammad and His Message in the Poetry of Muḥammad Iqbal - Mohd. Shamsuddin, Salahuddin; H. Asmad, Arman Bin; Hj. Ahmad, Siti Sara Binti (Advances in Social Sciences Research Journal, 2019)
There are many poems in the praise of the Prophet and his message in every language of Muslim peoples, but this research deals with this issue in the poetry of Muḥammad Iqbal in Urdu and Persian only. The methodology used in this research is the descriptive analytical approach, which is appropriate to such topics. Islamic Poet Muḥammad Iqbal addressed the praise of the Prophet and his message in a unique way distinguishes him from the other poets in the Islamic world. It is known that the Holy Quran is an intellectual miracle of the entire human world, but Iqbal believes that the sensory miracles of prophet can be happened also, as being the prophet the best of all creatures or in the Sufi term: (The Complete Man) who derives his strength from God with the divine love. Iqbal addresses the Prophet and says: "You are the guarded tablet, you are the pen and you are the book." This is a unique method of praising indicates a broad mystical meaning, because "the guarded tablet, the pen and the book" are some special terms that are referred to the worlds of divine knowledge in Sufism. It means that all of the science and knowledge that the Prophet had was from these worlds of divine knowledge. In his poetry Iqbal dealt with the multiple positions to the life of the Prophet and his miracles, but a large number of his poems can be considered a part of his philosophy in the human self.